The Effect of Internal Control Systems and Integrity Zones on Fraud Prevention: The Moderating Role of Transformational Leadership - Purnamasari, Nurma Safrilia; Haryanto, Haryanto (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to examine fraud prevention in Indonesian government institutions by analyzing the influence of internal control systems and integrity zones, as well as the moderating role of transformational leadership. The population consists of civil servants working in a central government ministry that has implemented integrity zone initiatives. Using purposive sampling, 375 valid responses were obtained from employees involved in financial management, supervision, and administrative functions. A quantitative approach was applied through structured questionnaires, and data were analyzed using variance-based structural equation modeling. The results indicate that internal control systems have a positive and significant effect on fraud prevention by enhancing transparency and accountability. Integrity zones also demonstrate a significant positive influence by strengthening governance and promoting anti-corruption values. Transformational leadership does not significantly moderate the relationships between internal control systems, integrity zones, and fraud prevention. These findings suggest that fraud prevention in government institutions is more strongly associated with formal governance mechanisms, highlighting the importance of strengthening internal controls and integrity-based reforms to enhance anti-fraud effectiveness.